Perancangan Museum Life After Death Dengan Pendekatan Utopia Arsitektur - Fadia Adila; Yohannes Firzal; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Humans will experience 5 stages of life starting from the stage of nothingness, the stages of the womb stage, the stages of life in the world, the stages of the barzakh realm, and finally, the stages of the afterlife Museum is an institution that is intended for the general public. A museum refers to a building that holds ancient history, cultural heritage, and various types of living and non-living objects. In this plan, a museum of the development of life will be designed, which will display 5 phases of the history of the development of human life so that people can catch up. The museum will be a media for documentation, education, and recreation. This end-of-time museum planning uses an architectural utopia approach that is by the function of the design. This is because life after death is a very perfect and real delusion. Architectural utopia is a contradiction in reality that has continuity with the design function. Keywords: Museums, End Times, Utopia Architecture